Evaluación de la salud del suelo bajo monocultivo de papa - Delaporte Quintana, Paola Adriana Georgina; Quiroga, Rolando Jose; Garcia, Jose Antonio; Portocarrero, Rocio (Asociación de Biología de Tucumán, 2025)
Poster y resúmen